SRAP analysis of brown planthopper (Nilaparvata lugens) populations maintained on differential rice host varieties - Chaerani Chaerani; Ahmad Dadang; Fatimah Fatimah; Bahagiawati Amir Husin; Sutrisno Sutrisno; Muhamad Yunus (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Chaerani, Dadang A, Fatimah, Husin BA, Sutrisno, Yunus M. 2021. SRAP analysis of brown planthopper (Nilaparvata lugens) populations maintained on differential rice host varieties. Biodiversitas 22: 4266-4272. Brown planthopper (Nilaparvata lugens Stål) biotypes differ in virulence to rice varieties carrying different Bph resistance genes. These biotypes are reported can be genetically discriminated against using DNA markers. Four brown planthoppers (BPH) populations, which displayed two virulence phenotypes, have been produced by selection and adaptation on four differential host varieties. Sequence-related amplified polymorphism (SRAP) marker preferentially amplifies the coding regions in the genome and, thus, can discriminate the observed virulence variations among those populations. This study aimed to analyze the genetic variation of four developed BPH populations using SRAP markers. Genetic analysis of a total of 40 BPH females with 18 polymorphic primers revealed equal genetic diversity parameter values among populations (Na: 1.1 to 1.4, Ne: 1.2 to 1.3, I: 0.22 to 0.29, He: 0.14 to 0.18, and UHe: 0.15 to 0.19). Analysis of population structure by AMOVA indicated low genetic variation among populations (9%). Still, pairwise PhiPT population values between all pairs of the population revealed the presence of moderate genetic differentiations (PhiPT ranged from 0.57 to 0.133, P<0.01). Two partial clusters in plots of PCoA were corresponded to two virulence groups, indicating the ability of SRAP markers to discriminate virulence phenotype. Further selection and adaptation are expected can form four desired virulence patterns with complete genetic separation among the population before its application as resistance screening agents of rice lines.